Implementation Of Property Rights Limitation Provisions In Community Life In Bantul District Special Region Of Yogyakarta - Prihati Yuniarlin; Endang Heriyani (Al-Makki Publisher, 2022)
Property rights are material rights that are absolute. Based on Article 570 of the Criminal Code, property rights are rights that are fully and freely used, however, the freedom to use property rights is not unlimited, but there are limitations. The problem in this research is: How is the application of the provisions on the limitation on the use of property rights in social life in Bantul Regency, DIY? The results showed that the application of restrictions on the use of property rights in people's lives in Bantul Regency can be seen in the Yogyakarta State Administrative Court Decision Number 04/G/2013/PTUN.YK which was corroborated by the Surabaya State Administrative High Court Decision Number: 149/B/ 2013/PT. TUN. SBY. The decision was declared null and void and revoked the Decree of the Head of the Bantul Regency Licensing Service Number: 3497/DP/001/XI/2012 concerning Disturbance Permits for